HOS-ocean: Open-source solver for nonlinear waves in open ocean based on High-Order Spectral method - Ducrozet, Guillaume; Bonnefoy, Félicien; Le Touzé, David; Ferrant, Pierre (Computer physics communications, 2016)
HOS-ocean is an efficient High-Order Spectral code developed to solve the deterministic propagation of nonlinear wavefields in open ocean. HOS-ocean is released as open-source, developed and distributed under the terms of GNU General Public License (GPLv3). Along with the source code, a documentation under wiki format is available which makes easy the compilation and execution of the source files. The code has been shown to be accurate and efficient. Program title: HOS-ocean Catalogue identifier: AEZS_v1_0 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AEZS_v1_0.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland Licensing provisions: GNU General Public License, version 3 No. of lines in distributed program, including test data, etc.: 30332 No. of bytes in distributed program, including test data, etc.: 2656194 Distribution format: tar.gz Programming language: Fortran. Computer: Tested on Intel Xeon E5504 and Intel Core i7. Operating system: Any system with a Fortran compiler: tested on Linux, OS X and Windows 7. RAM: From several MB up to several GB, depending on problem (512×512, M=3: 385 MB and 256×256, M=3: 99 MB) Classification: 4.12. External routines: FFTW 3.3.4 [1], LAPACK [2] and makedepf90 (linux.die.net/man/1/makedepf90) Nature of problem: HOS-ocean has been developed to study the propagation of highly nonlinear sea-states over large domains and long duration. Solution method: HOS-ocean is an implementation of the High-Order Spectral method, which solves the problem formulated on the free surface by means of a pseudo-spectral method. Restrictions: HOS-ocean is dedicated to the propagation of wave fields in infinite and finite constant depth, the evolution over variable bathymetry is not treated. Furthermore, simulations are restricted to non-breaking waves. Running time: 2D simulation of irregular wavefield with Nx=1024 modes and an HOS order M=5: t≅2.010−1s per wave period 3D simulation of irregular wavefield with Nx=256, Ny=256 modes, an HOS order M=3: t≅10s per wave period. References:[1]Matteo Frigo and Steven G. Johnson. The design and implementation of FFTW3. Proceedings of the IEEE, 93(2):216–231, 2005. Special issue on “Program Generation, Optimization, and Platform Adaptation”.[2]E. Anderson, Z. Bai, C. Bischof, S. Blackford, J. Demmel, J. Dongarra, J. Du Croz, A. Greenbaum, S. Hammarling, A. McKenney, and D. Sorensen. LAPACK Users’ Guide. Society for Industrial and Applied Mathematics, Philadelphia, PA, third edition, 1999.